Banking relationship and credit terms: empirical evidence from Portuguese small firms - Matias, Miguel Neves (2014)
Based on a sample of Micro and Small-sized Enterprises (MSE) financed by a large Portuguese bank, this study seeks to assess the importance of the banking relationship for MSE to obtain better credit terms, i.e. higher credit limit, lower risk premium and less probability that collateral must be provided. We conclude that long term banking relationship alone is not important for firms to obtain better bank credit terms. However, greater borrowing concentration allows MSE to obtain a lower risk premium and a higher limit of credit. The magnitude of these impacts are affected by some specificities related to firm size, economic-financial performance and the position of the lending bank in the local banking market.